Vitamin E partially ameliorates cyclophosphamide-induced nephrotoxicity in rats - Cuce, Gokhan; Esen, Hacı Hasan; Koc, Tugba; Canbaz, Halime Tuba; Limandal, Cisem; Kalkan, Serpil; Gürbilek, Mehmet (Progress in Nutrition, 2016)
Purpose: Cyclophosphamide (CP) is a widely used anti chemotherapeutic drug, which causes nephrotoxicity due to its toxic metabolites. This study was carried out to assess the effects of vitamin E on cyclophosphamide induced renal toxicity in rats. Model: Twenty-eight Wistar albino rats were assigned to four groups, which were given 20 mg/kg CP, 20 mg/kg CP + 100 mg/kg vitamin E, 100 mg/kg vitamin E, or 20 mg/kg isotonic sodium chloride solution intraperitoneally each day for 7 days. Effects were assessed by histology of the kidney, TUNEL assay and measurement of serum uric acid and creatinine. Results: Cyclophosphamide significantly increased glomerular inflammation, edema, congestion and tubular degeneration, TUNEL positive cells, while addition of vitamin E significantly decreased glomerular inflammation, edemaand TUNEL positive cells. Cyclophosphamide did not affect urea and creatinine levels, which may due to the absence of renal necrosis. Conclusion: Vitamin E application appears to partially ameliorate Cyclophosphamide induced renal toxicity.